Juridical Analysis of Delegated Authority from Anesthesiologist to Nurses in Performing Anesthetic Procedures - Chiko, Syahruddin; Jamaludin, Ahmad (Research Horizon, 2025)
The growing public demand for professional and legally accountable healthcare services, coupled with the limited availability of anesthesiology personnel, has led to the increasingly common practice of delegating anesthetic procedures to nurses, creating significant legal controversy that requires thorough examination. This study examines the legal aspects of the delegation of authority from anesthesiologists to nurses in performing anesthesia or sedation. The method used in this study is normative legal research, which is research using legislation covering three layers of legal science consisting of legal dogmatics, legal theory, and legal philosophy. The results of the discussion found that from a positive legal perspective, the delegation of authority from anesthesiologists to nurses to perform anesthesia within the scope of anesthesia services is contrary to the legal norms or rules as stipulated in Law Number 36 of 2014 concerning Health Workers and also Law-Law Number 38 of 2014 concerning Nursing, which is Lex Specialis for nurses, and Law Number 17 of 2023 concerning Health. Therefore, the delegation of authority from anesthesiologists to nurses can be categorized as an unlawful act because anesthesia is a special medical procedure that can only be delegated to health workers who have been authorized by the government.